Busy betty eaudiobook - Witherspoon, Reese (Busy Betty., 2022)
A New York Times bestseller! From Academy Award–winning actress, founder, and bestselling author, Reese Witherspoon, comes Busy Betty , a story about a creative, curious, and exuberant young girl who has big plans and an even bigger heart. Busy Betty has always been busy . . . even when she was just a baby! When Betty gives Frank a big hug, she realizes he needs a bath, PRONTO! Her best friend, Mae, is coming over, and Betty can’t have the smelliest dog in the whole world! But giving Frank a bath is harder than she thought and just when everything seems impossible, with Mae’s help, Betty learns she can accomplish anything with perseverance, teamwork, and one great idea. From Reese Witherspoon comes a smart and larger-than-life character who encourages young readers to celebrate what makes them unique and realize that anything is possible! Praise for Busy Betty: "A fun and high-spirited story for the fans of Fancy Nancy , Pinkalicious , or Freckleface Strawberry ."— School Library Journal "An earnest and unabashed celebration of youthful entrepreneurial zeal that feels very of the moment." — Publishers Weekly "Extreme angles effectively convey a sense of perpetual motion. . . . Witherspoon’s rollicking text never holds back . . . . as Betty says, “Being busy is a great way to be.” Young readers are sure to agree."— Kirkus reviews